Krisis Energi Eropa Pasca-PerangRusia–Ukraina: Analisis StrategiKetahanan Energi Uni Eropa - M.osama Ergi setiawan; Kezya Putri safira; aliyyah early cecilia Herman; Yulia Rimapradesi (Jurnal Keamanan Nasional, 2025)
The escalation of the Russia–Ukraine conflict in February 2022 catalyzed a profound energy crisis across Europe, exposing the structural vulnerabilities of the European Union (EU) resulting from its acute dependency on Russian fossil fuel imports. According to data from the European Commission and the International Energy Agency (IEA), Russia supplied approximately 40% of the EU’s natural gas prior to the conflict—a condition that fundamentally destabilized regional energy security and economic stability. This study analyzes the EU’s strategic responses to the crisis and evaluates the efficacy of these policies in mitigating energy reliance on Russia. Employing a qualitative descriptive-analytical framework, the research synthesizes secondary data from international institutional reports and academic literature on energy geopolitics. The findings demonstrate that through supply diversification, the acceleration of the renewable energy transition, enhanced energy efficiency, and strengthened regional solidarity—specifically via the REPowerEU initiative and the Green Deal Industrial Plan—the EU successfully reduced its dependence on Russian energy to below 10% during the 2022–2023 period. Oil imports from Russia also dropped from 27% to 6%, while coal imports fell to zero. These results indicate that the energy crisis served as a critical driver for regional policy transformation, notwithstanding persistent challenges such as high transition costs and disparate adaptation capacities among member states.